KINETIC RATES OF AMORPHOUS AS2S3 OXIDATION AT 25 TO 40°C AND INITIAL PH OF 7.3 TO 9.4 - Lengke M.F.; Tempel R.N. (My University, 2001)
The experimental studies of As2S3 (am) oxidative dissolution were investigated by use of particle sizes of 8 to 44 μm in a mixed flow reactor at 25 to 40°C and initial pH 7.3 to 9.4 to determine the effect of dissolved oxygen content, temperature, sulfate, and pH at 0.01 M ionic strength. Most experiments ran for ~30 h; however, some longer (52 h) and shorter (6-10 h) experiments were also conducted. In most experiments, the As and S release rates had reached an apparent steady state after 20 h. For most experiments, oxidation became stoichiometric after a steady state condition was achieved. The arsenic and sulfur release rates after 20 h in most experiments are in the order of 2.70 x 10-10 to 4.90 x 10-9 mol m-2 s-1 in the presence of oxygen.The rate laws of As2S3 (am) oxidation were only determined for experiments that ran for ~30 h at 25 to 40°C and steady state pH 6.9 to 7.9 and are given as follows: Rate law:Activation energy: DE-01R(As)=10-16.77[DO]0.42[H+]-1.2616.8+/-5.0 kJ mol-1 R(S)=10-16.99[DO]0.35[H+]-1.2516.3+/-5.4 kJ mol-1, where R is the rate of As2S3 (am) destruction (mol m-2s-1), [DO] is the concentration of dissolved oxygen (M), and [H+] is the concentration of protons (M). The low activation energy of As2S3 (am) oxidative dissolution indicates diffusion control as the dominant mechanism. Moreover, most solid surfaces after the experiments appear smooth and undisturbed.In all experiments, As(III) is present in proportions ranging from ~49 to 92% of total As at steady-state conditions. Sulfur oxyanions occurred as sulfate (SO42-), sulfite (SO32-), and polythionates (SnO62-) where polythionates are found to be the dominant sulfur species. The acid generated from As2S3 (am) at 25°C and pH 7 to 9 can be expressed as follows: DE-0.2[H+]prod=7.89[H+]initial+(2.37x10-7), where [H+]prod is the proton release from the oxidation of As2S3 (am) (mol/g), [H+]initial is the initial amount of proton, and 2.37 x 10-7 is an empirical factor.